Gasification Burner Performance Test Using Bio-Coal Fuel - N. Nurhadi; Yoke Pribadi Kornarius; Slamet Handoko; Johannes K. Sirait; Muhamad Azhar Lutfi (Jurnal Indonesia Sosial Teknologi, 2023)
Fuel for high-energy solid fuel combustion systems must meet abundant availability, affordability, and environmental friendliness criteria, particularly having low greenhouse gas emissions. One type of fuel that meets these criteria is bio-coal. Gasification burners employ staged combustion techniques that enhance combustion efficiency and reduce the formation of harmful substances, making them more environmentally friendly. This article discusses the performance testing of gasification burners using bio-coal as fuel, with variable primary air flow rates of 25, 30, 35, 40, and 50 m3/hour and biomass percentages in the bio-coal of 25%, 50%, and 75% by weight. The parameters observed are burner capacity, temperature, and CO2 gas emission factor. The experimental results show that increasing the air flow rate from 25 to 35 m3/hour significantly increases burner capacity and temperature, while further increasing the primary air flow rate to 50 m3/hour results in a gradual increase in burner capacity. The experiments also indicate that increasing the biomass percentage in the bio-coal slightly increases burner capacity and temperature due to the similar calorific values of palm pellet and coal used. The gasification burner technology developed by BBP Tekmira has proven to operate effectively within a capacity range of 8 to 20 kg/hour for bio-coal fuel with biomass percentages ranging from 25% to 75% by weight, producing burner temperatures between 805 and 933 degrees Celsius. Using bio-coal for gasification burners has also been shown to reduce greenhouse gas emissions when the biomass percentage in bio-coal exceeds 64%.